(untitled) (Baghdad Science Journal, 2021)
Human cytomegalovirus (CMV) is the globally highly prevalent herpesvirus worldwide. CMV infects populations of all ages according to the Center for Disease Control and Prevention (CDC) and World Health Organization (WHO). CMV infections remain the most common viral complication potentially multiple in humans and are a major cause of congenital normality in women, which is why they are critical for diagnosis in several times when it happens during pregnancy. Pregnant women with CMV infection can be in charge of abortion or congenital expandaedby. This study involves the collection a total of (90) samples taken from each aborted and pregnant woman (70 with abortion cases and 20 of pregnant without history of abortion as control subjects) referring to Babylon teaching hospital for Maternity and Children, covering a period from (October 2018 to March 2019) to investigate the occurrence of Cytomegalovirus (CMV) in Babylon city. Patients and controls were evaluated for IgG, IgM antibodies and anti-HCMV IgG, IgM for (90) subjects were controlled in this study using the Enzyme Immunoassay Test Kit and read by enzyme - linked immunosorbent analyze (ELISA). In addition the polymerase chain reaction (PCR) DNA detection for CMV are based on the amplification of pathogen genomes in a particular region using different primers. The Chi-square test was used to analyze the data. The results show among 90 samples, women were evaluated for CMV infection, the seroprevalence titer was significantly higher at P <0.05 in seropositive cases ranging from 62(89%) toward positive CMV IgG, while the 65 (93%) of patients were positive CMV IgM from (70) women with abortions. By contrast, the results obtained from the controls were 9 (45%) subjects seropositive for IgG and all of them were seronegative with IgM. The anti – HCMV IgG finding showed high positivity that represents the furthermost of CMV infections among females through ages ranging between 20-29 years. Furthermore, the outcomes of molecular detection showed that a small number of samples 13 (19%) were HCMV DNA detectable in aborted women less than in pregnant women 3 (15%).